Letters on P-Relations, 1992–1997. Issue 3 (2nd September 2022) - Douthett, Jack; Cohn, Richard; Zanuttini-Frank, Dani
Abstract : Jack Douthett wrote a number of letters to John Clough and Richard Cohn concerning Cohn's "P-Relations, " single-semitone voice-leading relationships. The ideas in these letters led to graph-theoretic and geometric models. The following selection has been edited and prepared for publication by Richard Cohn and Dani Zanuttini-Frank.